2021
DOI: 10.1186/s13756-021-00965-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of antimicrobial resistance and its clinical implications in Ethiopia: a systematic review

Abstract: Background Antimicrobial resistance is one of the major public health challenges in Ethiopia. However, there is no comprehensive summary of existing AMR data in the country. Aim To determine the prevalence of antimicrobial resistance and its clinical implications in Ethiopia. Methods A systematic literature search was performed on the PubMed/Medline database. Original studies on antimicrobial resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 26 publications
(19 reference statements)
2
30
1
2
Order By: Relevance
“… 6 The poor hygiene along with the growth in immunocompromised patients are further exaggerating the AMR in Sub-Saharan Africa (SSA). 6 It was claimed that the majority of global antibiotic consumption between 2000 and 2015 was in LMICs, especially in SSA, mainly due to their high incidence of infectious diseases. Additionally, it was reported that most of the deaths are expected to be in SSA owing to their low financial capability of the health care system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 6 The poor hygiene along with the growth in immunocompromised patients are further exaggerating the AMR in Sub-Saharan Africa (SSA). 6 It was claimed that the majority of global antibiotic consumption between 2000 and 2015 was in LMICs, especially in SSA, mainly due to their high incidence of infectious diseases. Additionally, it was reported that most of the deaths are expected to be in SSA owing to their low financial capability of the health care system.…”
Section: Introductionmentioning
confidence: 99%
“…5 The current situation in African countries is catastrophic and very difficult to precisely describe since very few countries give a regular national surveillance report on AMR. 6 The poor hygiene along with the growth in immunocompromised patients are further exaggerating the AMR in Sub-Saharan Africa (SSA). 6 It was claimed that the majority of global antibiotic consumption between 2000 and 2015 was in LMICs, especially in SSA, mainly due to their high incidence of infectious diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Resistance to amoxicillin-clavulanic acid, amikacin, cefepime, cefotaxime, ceftriaxone, cefuroxime, cipro oxacin, gentamycin, meropenem, and trimethoprimsulfamethoxazole was signi cantly higher in Syria than in Ethiopia. However, resistance to nitrofurantoin was slightly higher in Ethiopia [30].…”
Section: Discussionmentioning
confidence: 83%
“…Antimicrobial resistance is also on the rise, and there have been instances of hospitalization and mortality as a result of it [ 40 ]. As a result, it is possible that Ethiopia's antimicrobial resistance danger is being exacerbated by the over-prescription of antibiotics [ 41 ]. Antibiotic resistance has a considerable impact on medicine accessibility and healthcare financing in Ethiopia because of the high prevalence of poverty and limited resources [ 42 ].…”
Section: Discussionmentioning
confidence: 99%